The Role of Education in the Development of Jawi in Brunei Darussalam - A. Rahman, Sri Kartika; Ampuan Hj Tengah, Ampuan Hj Brahim; Makmun, Rozaiman (Journal of Al-Tamaddun, 2022)
This literary research aims to discuss the role of education in the history and development of the usage of the Jawi script in Brunei. This discussion is divided into six phases. The first phase is the use of Jawi in education after the arrival of Islam. The second phase is its use during the early development of education between 1914 and 1941. The third phase is during the Japanese occupation era from 1942 until 1945. The fourth phase is in the pre-independence era between 1943 and 1983. The fifth phase is in the Bilingual Education policy from 1984 until 2007, and the last phase is during the National Education System for the 21st Century Policy, from 2008 until today. The researcher discovered that the role and importance of Jawi in the field of education remain relevant, especially in preserving it as the heritage and identity of the Malay race.